2010
DOI: 10.17221/38/2010-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of porcine oocytes is associated with zona pellucida glycoprotein 3 and integrin beta 2 protein levels--

Abstract: ABSTRACT:The morphology and quality of oocytes is set during oo-and folliculo-genesis, and is completed during final maturation. Early embryonic development is associated with the morphology of the cumulus-oocytecomplex (COC). However, current knowledge of the possible relationships between oocyte morphology and the level of proteins within the oocyte, which may reflect fertilization ability, is insufficient. Using western-blot analysis and confocal microscopic observation, we determined the levels of integrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
7
2
Order By: Relevance
“…The same pattern has been observed in mouse oocytes, as the ZP3 transcript increases gradually from primordial to small antral follicles then decreases in the large antral follicles (Pan et al, ). Moreover, in porcine oocytes, the ZP3 protein level has been reported to be significantly higher in oocytes isolated from large compared to small follicles (Antosik et al, ). In agreement with our findings, these results could suggest that ZP3 is accumulated in the early growing oocyte, then it is utilized and accumulated as a protein in the fully grown oocytes to build the zona pellucida and support oocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…The same pattern has been observed in mouse oocytes, as the ZP3 transcript increases gradually from primordial to small antral follicles then decreases in the large antral follicles (Pan et al, ). Moreover, in porcine oocytes, the ZP3 protein level has been reported to be significantly higher in oocytes isolated from large compared to small follicles (Antosik et al, ). In agreement with our findings, these results could suggest that ZP3 is accumulated in the early growing oocyte, then it is utilized and accumulated as a protein in the fully grown oocytes to build the zona pellucida and support oocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the pig have suggested that developmental potential and fertilization ability may be strongly related to briliant crezyl blue test (BCB) staining, oocyte morphology and follicular size (Kölle et al , 2007; Antosik et al , 2010; Kempisty et al , 2011). The experiments examining the expression and/or distribution of zona pellucida proteins are currently of high significance due to the low number of fully matured canine oocytes recovered in vitro as well as the decreased fertilization rate.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are encoded by ZP genes, ZP1, ZP2, ZP3 and ZP4 (Gupta et al, 2012). ZP2 functions as the secondary receptor and plays, compared to ZP3, a subordinate role during the initial steps of fertilization (Jackowska et al, 2009;Antosik et al, 2010;Ikawa et al, 2010;Kempisty et al, 2011;Kempisty et al, 2012). ZP2 functions as the secondary receptor and plays, compared to ZP3, a subordinate role during the initial steps of fertilization (Jackowska et al, 2009;Antosik et al, 2010;Ikawa et al, 2010;Kempisty et al, 2011;Kempisty et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oocyte quality is one of the most important factors that affects the outcome of porcine embryo development (Antosik et al , 2010). Although many kinds of cloning animals have been produced during recent decades, objective criteria for selecting competent oocytes remain elusive.…”
Section: Introductionmentioning
confidence: 99%